A Coaxial Dual-element Focused Ultrasound Probe for Guidance of Epidural Catheterization: An Experimental Study. (September 2017) - Dong, Guo-Chung; Chiu, Li-Chen; Ting, Chien-Kun; Hsu, Jia-Ruei; Huang, Chih-Chung; Chang, Yin; Chen, Gin-Shin
Ultrasound guidance for epidural block has improved clinical blind-trial problems but the design of present ultrasonic probes poses operating difficulty of ultrasound-guided catheterization, increasing the failure rate. The purpose of this study was to develop a novel ultrasonic probe to avoid needle contact with vertebral bone during epidural catheterization. The probe has a central circular passage for needle insertion. Two focused annular transducers are deployed around the passage for on-axis guidance. A 17-gauge insulated Tuohy needle containing the self-developed fiber-optic–modified stylet was inserted into the back of the anesthetized pig, in the lumbar region under the guidance of our ultrasonic probe. The inner transducer of the probe detected the shallow echo signals of the peak-peak amplitude of 2.8 V over L3 at the depth of 2.4 cm, and the amplitude was decreased to 0.8 V directly over the L3 to L4 interspace. The outer transducer could detect the echoes from the deeper bone at the depth of 4.5 cm, which did not appear for the inner transducer. The operator tilted the probe slightly in left-right and cranial-caudal directions until the echoes at the depth of 4.5 cm disappeared, and the epidural needle was inserted through the central passage of the probe. The needle was advanced and stopped when the epidural space was identified by optical technique. The needle passed without bone contact. Designs of the hollow probe for needle pass and dual transducers with different focal lengths for detection of shallow and deep vertebrae may benefit operation, bone/nonbone identification, and cost.